News and Analysis : Early failure can lead to future success. (4th June 2019) - Allen, Michael
Abstract: When it comes to science, success does not always beget success. That is at least according to researchers in the US who claim that setbacks at the start of a scientist's career could – counterintuitively – lead to success later.